Професійний імідж викладача університету очима студента - Болотова, Вікторія Олександрівна; Ляшенко, Наталія Олександрівна (Класичний приватний університет, 2018)
У статті розглянуто сутність поняття професійного іміджу викладача університету, базові елементи його зовнішнього та внутрішнього аспектів. Наведено дані конкретного соціологічного дослідження, результати якого виявляють низку важливих професійних та моральних якостей на основі яких будується імідж викладача в свідомості студентів (на прикладі НТУ "ХПІ"), вимірюються найбільш суттєві розбіжності між ідеальним та реальним іміджем викладача.

The research of the professional image of high school lecturer is more relevant, due to the transition to a democratic, partner style of teaching, increasing freedom of students in the choice of academic disciplines and lecturers itself. However, the problem of forming a professional image of a lecturer of higher education has not yet received a broad and holistic analysis within the framework of sociological research, which determines the relevance of this article. The main purpose of the article is to identify the basic characteristics of the ideal and real professional image of the modern university lecturer in the minds of students, for example, NTU "KhPI" and the allocation of factors that predetermine of them. Image as a definition is understood as a representation of the objects image (the individual, organization, subject and phenomenon). That objects image contains the information and evaluation parts and is formed for the individual (as a representative of the target audience) on the basis of its value orientations and stereotypical settings, activities the object and prompts the individual for certain actions. Professional image as a definition – a personified image of the representative of the profession, that is, a generalized emotionally colored image of a typical professional who has a symbolic nature and influences others. The basic elements of the internal aspect of professional image are professional knowledge and skills, intellectual and moral – ethical qualities. The external aspect of the professional image includes the appearance (appearance, hairstyle, style of clothing, etc.), verbal (speech quality), nonverbal (behavior, speed of speech), environmental (state and equipment of the working city) and a real image. The questionnaire survey of 431 students of the National Technical University "Kharkiv Polytechnic Institute" showed that professional qualities are the most important for forming a professional image of a lecturer. According to the students, an ideal lecturer should be able to easily and easily present material, submit it logically, consistently, reasonably and fairly evaluate the work of students. Among the external characteristics are the literacy of the language and behavior of the lecturer. Regards to moral qualities, the most important among them, according to students, is justice and responsibility. The comparison of the images of the ideal lecturer of the university and the real lecturer of the NTU "KhPI" in the minds of the students showed that the appearance of the lecturer corresponds to the ideal views of the students. With respect to the assessment of moral qualities, the greatest difference is observed between such personal qualities as justice, responsibility, honesty and punctuality. There are also significant differences between the importance for students of such characteristics as the ability to teach material interestingly, to boost the activity of students in the classroom and the actual state of affairs. The obtained results allowed to provide a number of recommendations for improving the image of lecturers and bringing their real image closer to the ideal.
Professional Image of a University Teacher Through the Eyes of a Student
Keywords: навчальний процес; педагогічна діяльність; моральні якості; складові іміджу; ідеальний імідж; реальний імідж; вища освіта; professional image; ideal image; real image; components of the image